(3) Differentiating both sides of
![2x^{3/2} + y^{3/2} = 29](https://tex.z-dn.net/?f=2x%5E%7B3%2F2%7D%20%2B%20y%5E%7B3%2F2%7D%20%3D%2029)
with respect to <em>x</em> gives
![3x^{1/2} + \dfrac32 y^{1/2} \dfrac{\mathrm dy}{\mathrm dx} = 0](https://tex.z-dn.net/?f=3x%5E%7B1%2F2%7D%20%2B%20%5Cdfrac32%20y%5E%7B1%2F2%7D%20%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%20%3D%200)
Solve for d<em>y</em>/d<em>x</em> :
![\dfrac32 y^{1/2} \dfrac{\mathrm dy}{\mathrm dx} = -3x^{1/2} \\\\ \dfrac{\mathrm dy}{\mathrm dx} = \dfrac{-3x^{1/2}}{\frac32y^{1/2}} = \dfrac{-2x^{1/2}}{y^{1/2}} = -2\sqrt{\dfrac xy}](https://tex.z-dn.net/?f=%5Cdfrac32%20y%5E%7B1%2F2%7D%20%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%20%3D%20-3x%5E%7B1%2F2%7D%20%5C%5C%5C%5C%20%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%20%3D%20%5Cdfrac%7B-3x%5E%7B1%2F2%7D%7D%7B%5Cfrac32y%5E%7B1%2F2%7D%7D%20%3D%20%5Cdfrac%7B-2x%5E%7B1%2F2%7D%7D%7By%5E%7B1%2F2%7D%7D%20%3D%20-2%5Csqrt%7B%5Cdfrac%20xy%7D)
Then the slope of the tangent line to the curve at (1, 9) is
![\dfrac{\mathrm dy}{\mathrm dx} = -2\sqrt{\dfrac19} = -\dfrac23](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%20%3D%20-2%5Csqrt%7B%5Cdfrac19%7D%20%3D%20-%5Cdfrac23)
The equation of the tangent line would then be
<em>y</em> - 9 = -2/3 (<em>x</em> - 1) ==> <em>y</em> = -2/3 <em>x</em> + 29/3
(4) The slope of the tangent line to
![y=\dfrac{ax+1}{x-2}](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7Bax%2B1%7D%7Bx-2%7D)
at a point <em>(x, y)</em> on the curve is
![\dfrac{\mathrm dy}{\mathrm dx} = \dfrac{a(x-2)-(ax+1)}{(x-2)^2} = -\dfrac{2a+1}{(x-2)^2}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%20%3D%20%5Cdfrac%7Ba%28x-2%29-%28ax%2B1%29%7D%7B%28x-2%29%5E2%7D%20%3D%20-%5Cdfrac%7B2a%2B1%7D%7B%28x-2%29%5E2%7D)
When <em>x</em> = -1, we have a slope of 2/3, so
-(2<em>a</em> + 1)/(-1 - 2)² = 2/3
Solve for <em>a</em> :
-(2<em>a</em> + 1)/9 = 2/3
2<em>a</em> + 1 = -18/3 = -6
2<em>a</em> = -7
<em>a</em> = -7/2